Photocatalytic Activity Induced by Metal Nanoparticles Synthesized by Sustainable Approaches: A Comprehensive Review - Krishna, Prashanth Gopala; Chandra Mishra, Prabhu; Naika, Mutthuraju Mahadev; Gadewar, Manoj; Ananthaswamy, Prashanth Paduvarahalli; Rao, Srilatha; Boselin Prabhu, Sivadhas Rosejanet; Yatish, Kalanakoppal Venkatesh; Nagendra, Holenarasipura Gundurao; Moustafa, Mahmoud; Al-Shehri, Mohammed; Jha, Saurabh Kumar; et al. (Frontiers in Chemistry, 2022)
Nanotechnology is a fast-expanding area with a wide range of applications in science, engineering, health, pharmacy, and other fields. Among many techniques that are employed toward the production of nanoparticles, synthesis using green technologies is the simplest and environment friendly. Nanoparticles produced from plant extracts have become a very popular subject of study in recent decades due to their diverse advantages such as low-cost synthesis, product stability, and ecofriendly protocols. These merits have prompted the development of nanoparticles from a variety of sources, including bacteria, fungi, algae, proteins, enzymes, etc., allowing for large-scale production with minimal contamination. However, nanoparticles obtained from plant extracts and phytochemicals exhibit greater reduction and stabilization and hence have proven the diversity of properties, like catalyst/photocatalyst, magnetic, antibacterial, cytotoxicity, circulating tumor deoxy ribo nucleic acid (CT-DNA) binding, gas sensing, etc. In the current scenario, nanoparticles can also play a critical role in cleaning wastewater and making it viable for a variety of operations. Nano-sized photocatalysts have a great scope toward the removal of large pollutants like organic dyes, heavy metals, and pesticides in an eco-friendly and sustainable manner from industrial effluents. Thus, in this review article, we discuss the synthesis of several metal nanoparticles using diverse plant extracts, as well as their characterization via techniques like UV–vis (ultraviolet–visible), XRD (X-ray diffraction), SEM (scanning electron microscopy), TEM (transmission electron microscopy), FTIR (Fourier transform infrared spectroscopy), etc., and catalytic activity on various hazardous systems.